Investigations on the Essential oil of Cymbopogon giganteus from Beninfor its potential use as an anti-inflammatory agent - ALITONOU, GUY ALAIN; AVLESSI, FÉLICIEN; Sohounhloue, Dominique; Bessière, Jean Marie; MENUT, Chantal (My University, 2006)
The species of Cymbopogon giganteus is widely used in traditional medicine against several diseases . This study reports the inhibitory effect produced by the chemical constituents of the essential oil from leaves of C. giganteus of Benin, in vitro on 5-lipoxygenase. We assayed the antiradical scavenging activity of the sample by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The essential oil of C. giganteus was analyzed by GC and GC/MS. The major constituents were: trans-p-1(7),8-menthadien-2-ol (22.3%), cis-p-1(7),8-menthadien-2-ol (19.9%), trans-p-2,8-menthadien-1-ol (14.3%), cis-p-2,8-menthadien-1-ol (10.1%).
Keywords: • Essential oil; Cymbopogongiganteus; p-1(7); 8-Menthadien-2-ols; p-2; 8-Menthadien-1-ols; Anti-inflammatory activity; Antiradical activity